2018
DOI: 10.1002/jssc.201701151
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of food‐grade C‐phycocyanin from Arthrospira platensis and its determination in confectionery by HPLC with diode array detection

Abstract: C-Phycocyanin is the major phycobiliprotein in Arthrospira platensis, also known as Spirulina, which is a cyanobacterium used as a dietary supplement because of its powerful effects on body and brain. C-phycocyanin is a blue-colored accessory photosynthetic pigment with multiple applications in food industry as natural dye or additive, and in pharmaceuticals. This study presents a simple protocol for the extraction and purification of food-grade C-phycocyanin from Arthrospira platensis. The cell lysis of cyano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…Phycocyanin degradation by temperature (Antelo et al, 2008) and light (Jespersen et al, 2005) over time are potential causes of extraction efficiency loss that we considered minimal in our experiments because moss samples were always kept at cool temperature and in the dark during the extraction. Repeatability reported here are also similar to values reported in literature for pure culture (Kissoudi et al, 2018;Prates et al, 2018). Thus, our results show that the efficiency of cyanobacteria cell wall disruption is the principal factor that could affect the quality of phycocyanin measurements but that, overall, phycocyanin can be accurately and reliably quantified for large cyanobacterial cell density and moss mass ranges.…”
Section: Phycocyanin Extraction Methods Characterization and Validationsupporting
confidence: 90%
See 2 more Smart Citations
“…Phycocyanin degradation by temperature (Antelo et al, 2008) and light (Jespersen et al, 2005) over time are potential causes of extraction efficiency loss that we considered minimal in our experiments because moss samples were always kept at cool temperature and in the dark during the extraction. Repeatability reported here are also similar to values reported in literature for pure culture (Kissoudi et al, 2018;Prates et al, 2018). Thus, our results show that the efficiency of cyanobacteria cell wall disruption is the principal factor that could affect the quality of phycocyanin measurements but that, overall, phycocyanin can be accurately and reliably quantified for large cyanobacterial cell density and moss mass ranges.…”
Section: Phycocyanin Extraction Methods Characterization and Validationsupporting
confidence: 90%
“…In this study, all samples (cyanobacteria cultures and mosses) had phycocyanin concentration above those limits. Phycocyanin apparent recoveries in moss found in this study are close to the average apparent recovery reported in pure cultures (50-60%, Tavanandi et al, 2018) but optimized methods can reach 90-92% (Kissoudi et al, 2018;Prates et al, 2018;Tavanandi et al, 2018). Phycocyanin concentration measured in cyanobacteria cultures depends greatly on the extraction process (e.g., solvent, extraction time, cell wall disruption technique; Abalde et al, 1998;Reis et al, 1998).…”
Section: Phycocyanin Extraction Methods Characterization and Validationsupporting
confidence: 81%
See 1 more Smart Citation
“…The slides were incubated at room temperature with secondary antibody mixture (Alexa Fluor 594 goat anti-mouse antibody and Alexa Fluor 488 goat anti-guinea pig antibody). After staining the nucleus with 4′,6-diamidino-2phenylindole (DAPI), the slides were mounted and subjected to analysis using tetramethylrhodamine isothiocyanate (594 nm) or fluorescein isothiocyanate filters (488 nm) to measure the absorbance and fractions were collected according to the appearance of peaks in individual time points (37) .…”
Section: Islet Morphology After 9-days Treatment With Extract Of C Smentioning
confidence: 99%
“…Many procedures for the purification of CPC have been described in the literature, most relying on a combination of multiple purification steps, usually including ammonium precipitation, dialysis, and packed bed AEX chromatography to achieve CPC purities of up to 6.7 [26][27][28][29][30][31][32][33][34][35][36][37]. The AEX chromatography step alone in packed bed mode provides a purification factor ranging from 1.3 to 4.9.…”
Section: Initial Purity (A 620 /A 280 ) [-]mentioning
confidence: 99%